Improving treatment efficiency via photon optimizer (PO) MLC algorithm for synchronous single‐isocenter/multiple‐lesions VMAT lung SBRT - Sanford, Lana (J Appl Clin Med Phys, 2019)
PURPOSE: Elderly patients with multiple primary or oligometastases (<5 lesions) lesions with associated co‐morbidities may not retain their treatment position for the traditional long SBRT treatment time with individual isocenters for each lesion. Treating multiple lesions synchronously using a single‐isocenter volumetric arc therapy (VMAT) plan would be more efficient with the use of the most recently adopted photon optimizer (PO) MLC algorithm and improve the patient comfort. Herein, we quantified the clinical performance of PO versus its predecessor progressive resolution optimizer (PRO) algorithm for single‐isocenter/multiple‐lesions VMAT lung SBRT. MATERIALS AND METHODS: Fourteen patients with metastatic non‐small‐cell lung cancer lesions (two to five, both uni‐ and bilateral lungs) received a highly conformal single‐isocenter co/non‐coplanar VMAT (2–6 arcs) SBRT treatment plan. Patients were treated with a 6X‐FFF beam and Acuros algorithm with a single‐isocenter placed between/among the lesions, using PO for MLC optimization. Average isocenter to tumor distance was 5.5 ± 1.9 cm. Mean combined PTV derived from 4D‐CT scans was 38.7 ± 22.7 cc. Doses were 54 Gy/50 Gy in 3/5 fractions prescribed to 70%–80% isodose line so that at least 95% of the PTV receives 100% of prescribed dose. Plans were re‐optimized using PRO algorithm. Plans were compared via ROTG‐0915 protocol criteria for target conformity, heterogeneity and gradient indices, and dose to organs‐at‐risk (OAR). Additionally, total number of monitor units (MU), modulation factor (MF) and beam‐on time were compared. RESULTS: All plans met SBRT protocol requirements for target coverage and OAR doses. Comparison of target coverage and dose to the OAR showed no statistical significance between the two plans. PO had 1042 ± 753 (P < 0.001) less MU than PRO resulting in a beam‐on time of about 0.75 ± 0.5 min (P < 0.001) less, on average. For similar dose distribution, a significant reduction of beam delivery complexity was observed with PO (average MF = 3.7 ± 0.7) vs PRO MLC algorithm (average MF = 4.4 ± 1.3) (P < 0.001). CONCLUSIONS: PO MLC algorithm improved treatment efficiency without compromising plan quality when compared to PRO algorithm for single‐isocenter/multi‐lesions VMAT lung SBRT. Shorter beam‐on time can potentially reduce intrafraction motion errors and improve patient compliance. PO MLC algorithm is recommended for future clinical lung SBRT plan optimization.